2018
DOI: 10.4038/jnsfsr.v46i2.8418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethephon stimulation on natural rubber latex properties; new insight into ethephon stimulation

Abstract: tool to overcome issues such as high cost of production, plantation industries. When developing a protocol for ethephon effect on associated latex quality parameters. Therefore, this study elucidated the effect of ethephon on dry rubber yield rheological behaviour and physiological parameters. Five stimulated latex as the control. The results revealed that all the S/2 d3 harvesting system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…A tapping system and ethylene stimulation are the main tools for obtaining latex production in rubber plantations. However, this study showed that only four of 38 analyzed papers reported modification and evaluation of the suitability of the tapping system (Padjung et al, 2020;Pereira et al, 2018;Purwaningrum et al, 2019;Rukkhun et al, 2021 and five studies on ethylene stimulation (Attanayake et al, 2018;Long et al, 2018;Purwaningrum et al, 2019;Yunta & Dede, 2019;and Budiasih et al, 2020) Although much research has been published in these two fields, most of them were in journals unrecognized by Scopus. This suggests that research on these topics requires additional data such as LD and molecular analysis for a better explanation of the effect of tapping and stimulation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A tapping system and ethylene stimulation are the main tools for obtaining latex production in rubber plantations. However, this study showed that only four of 38 analyzed papers reported modification and evaluation of the suitability of the tapping system (Padjung et al, 2020;Pereira et al, 2018;Purwaningrum et al, 2019;Rukkhun et al, 2021 and five studies on ethylene stimulation (Attanayake et al, 2018;Long et al, 2018;Purwaningrum et al, 2019;Yunta & Dede, 2019;and Budiasih et al, 2020) Although much research has been published in these two fields, most of them were in journals unrecognized by Scopus. This suggests that research on these topics requires additional data such as LD and molecular analysis for a better explanation of the effect of tapping and stimulation.…”
Section: Discussionmentioning
confidence: 84%
“…The overlay map indicated that papers published in 2018 -2020 were directed to yield optimization and cost efficiency through tapping mechanization (Figure 3). The yield optimization was conducted through a tapping system and ethephon stimulation modifications supported by latex diagnosis (Attanayake et al, 2018;Yunta & Dede, 2019). In this period, studies on semi-automatic and automatic tapping Tendencia de investigación en la cosecha de látex del árbol del caucho (Hevea brasiliensis Muell.…”
Section: Current Research On Latex Harvesting Practicesmentioning
confidence: 99%
“…Stimulation-based low-intensity harvesting (LIH) systems are accepted worldwide as an agronomic tool to overcome the high cost of production, worker scarcity, and low economic lifespan of trees in rubber plantation industries [37]. Discoloration due to ethephon stimulation has been reported [34]; however, there is no evidence for the effect of ethephon concentration on the color of crepe rubber.…”
Section: Effect Of Ethephon Stimulation On Polyphenols Contentmentioning
confidence: 99%
“…Al respecto, An et al (2016) informan que la estimulación con etefón aumenta el rendimiento del látex tan pronto como se realiza su aplicación, el cual generalmente alcanza su máximo un tiempo después (7 días). Los estudios realizados por Attanayake et al ( 2018), donde se probaron diferentes concentraciones de etefón, señalan que los valores del CST en tratamientos estimulados disminuyeron significativamente, pasando de un 46 % sin estimulación a un 34 % cuando la concentración del estimulante fue del 5 %. Sin embargo, otros autores no han evidenciado respuestas significativas ante la aplicación del estimulante, tal como ocurrió en el estudio de Sainoi et al (2017), quienes probaron distintas frecuencias de aplicación de estimulante en plantas de caucho del clon PB261 y obtuvieron CST entre 52 y 55 %.…”
Section: Frecuencia Estimulaciónunclassified